Method for dealuminizing zeolite materials
Patent Information
- Application Number
- JP2023557450
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-03-19
- Filing Date
- 2022-03-18
- Publication Date
- 2026-10-13
- Estimated Expiration
- 2042-03-18
Abstract
Description
[Technical Field]
[0001] The present invention relates to a method for dealuminizing zeolite materials, and to the zeolite material itself that can be obtained or obtained according to said method. [Background technology]
[0002] Zeolites have many applications in the chemical industry, mostly as heterogeneous catalysts in various chemical and petrochemical processes. Generally, zeolites are crystalline aluminosilicates with a microporous structure. The special properties of zeolites stem, in particular, from their porous structure, which is a system of pores of molecular size that molecules can access, depending on their shape and size. Numerous zeolite skeletal structures are known, allowing them to function as selective heterogeneous catalysts in a variety of applications. The skeletal type and chemical composition determine the properties of the zeolite, such as ion exchange capacity, porosity, accessibility, acidity, and hydrophilicity or hydrophobicity.
[0003] Post-treatment methods are often employed to alter the properties of zeolite materials, such as their structure or composition. Common post-treatment methods include steam treatment, acid treatment, or basic treatment.
[0004] Steam treatment is often used in various selective reactions to enhance the activity and stability of zeolites to steam. For example, EP 0 013 433 A1 teaches the use of steam treatment to increase the activity of zeolites by increasing the Si / Al ratio. This steam treatment affects not only the Si / Al ratio but also the acidity / basicity and hydrophilicity / hydrophobicity of the zeolite.
[0005] Acid treatment has a similar effect, leading to the dealuminization of zeolites. Such acid treatments often involve organic acids such as acetic acid, propionic acid, and oxalic acid, or mineral acids such as hydrochloric acid, nitric acid, sulfuric acid, and phosphoric acid. For example, referring to WO 02 / 057181 A2, acid treatment is performed to increase the hydrophobicity of zeolite materials.
[0006] A combination of steam treatment and acid treatment is described in WO 2009 / 016153 A2. According to this document, phosphorus-modified molecular sieves with a low Si / Al ratio are subjected to high-temperature steam treatment before an acidic leaching step is carried out to remove Al from the zeolite framework. Steam treatment and acid treatment are also disclosed in WO 2012 / 137132 A1 concerning a method for producing acylation catalysts starting from zeolite beta.
[0007] Both steam treatment and acid treatment significantly affect the properties of zeolite materials. By subjecting zeolite materials containing both the tetravalent structural component YO2 and the trivalent structural component X2O3 to steam treatment and / or acid treatment, respectively, the molar ratio of YO2:X2O3 increases. However, it has been found that steam treatment and / or acid treatment reduce the crystallinity of the zeolite material. Therefore, both steam treatment and acid treatment result in a partial transformation of the zeolite material into an amorphous material. Thus, while the desired YO2:X2O3 molar ratio can be achieved through steam treatment or acid treatment, the resulting zeolite material has a major drawback, particularly in commercial applications.
[0008] On the other hand, WO 2014 / 060260 A1 relates to a method for dealuminizing zeolite materials, which includes subjecting the zeolite material to several treatment steps with aqueous acids, followed by at least one treatment with a liquid aqueous system having a pH in the range of 5.5 to 8 at a high temperature. According to this document, the aforementioned specific sequence enables dealuminization with reduced loss of crystallinity.
[0009] However, there is still a need for more time- and cost-efficient methods for dealuminizing zeolite materials, particularly in terms of the number of steps required to achieve the desired level of dealuminization without compromising the crystallinity of the zeolite material. [Prior art documents] [Patent Documents]
[0010] [Patent Document 1] EP 0 013 433 A1 [Patent Document 2] WO 02 / 057181 A2 [Patent Document 3] WO 2009 / 016153 A2 [Patent Document 4] WO 2012 / 137132 A1 [Patent Document 5] WO 2014 / 060260 A1 [Overview of the project] [Problems that the invention aims to solve]
[0011] Therefore, the object of the present invention was to provide an easy and highly efficient method for dealuminizing zeolite materials that does not exhibit the aforementioned drawbacks. [Means for solving the problem]
[0012] Surprisingly, it was found that zeolite materials containing YO2 and X2O3 could be dealuminized to the desired degree in fewer steps by a post-treatment process that included at least one treatment with a strongly acidic aqueous solution having a pH of less than 0.1 and at least one treatment with a liquid aqueous system having a pH in the range of 4 to 10. In particular, quite unexpectedly, it was found that dealuminization could be achieved in fewer steps without impairing the crystallinity of the resulting material by using a highly concentrated aqueous solution.
[0013] Therefore, the present invention is (1) A step of providing a zeolite material having a skeletal structure containing Y, X, and O, wherein Y is a tetravalent element and X is a trivalent element. (2) A step of providing an aqueous solution having a pH of less than 0.1, (3) a step of treating the zeolitic material provided in step (1) with the aqueous solution provided in step (2), (3.i) optionally, a step of washing the zeolitic material obtained in step (3), (3.ii) optionally, a step of drying the zeolitic material obtained in step (3) or (3.i), (3.iii) optionally, a step of calcining the zeolitic material obtained in step (3), (3.i) or (3.ii), (4) a step of treating the zeolitic material obtained in step (3), (3.i), (3.ii) or (3.iii) with an aqueous solution or solvent system, wherein the aqueous solution or solvent system has a pH in the range of 4 to 10, and the pH of the aqueous solution or solvent system refers to the pH before being brought into contact with the zeolitic material for the treatment, (4.i) optionally, a step of drying the zeolitic material obtained in step (4), (4.ii) optionally, a step of calcining the zeolitic material obtained in step (4) or (4.i), relates to a method for dealuminating a zeolitic material, comprising the steps of. [Mode for Carrying Out the Invention]
[0014] According to the present invention, the pH value of the aqueous solution preferably represents the pH of the aqueous solution determined at 20°C.
[0015] The zeolitic material provided in step (1) preferably has less than 1 wt%, more preferably less than 0.5 wt%, more preferably less than 0.1 wt%, more preferably less than 0.05 wt%, more preferably less than 0.01 wt%, more preferably less than 0.005 wt%, more preferably less than 0.001 wt% of H, based on 100 wt% of the total amount of Y, X and O contained in the zeolitic material +contains ionic non-framework elements other than the above. Further, the ionic non-framework elements preferably represent Na, more preferably Na and K, more preferably Li, Na and K, more preferably Li, Na, K and Cs, more preferably alkali metal cations, more preferably alkali metal and alkaline earth metal cations, and more preferably metal cations.
[0016] Preferably, the zeolitic material provided in step (1) contains one or more metals M, wherein the one or more metals M are selected from the group consisting of alkali metals, alkaline earth metals, and mixtures of two or more thereof, more preferably from the group consisting of alkali metals, more preferably from the group consisting of Li, Na, K, Rb, Cs, and mixtures of two or more thereof, more preferably from the group consisting of Li, Na, K, and mixtures of two or more thereof, more preferably the one or more metals M comprise Na and / or K, preferably Na, more preferably the one or more metals M consist of Na and / or K, preferably Na. Further, preferably, the zeolitic material provided in step (1) contains the one or more metals M in an amount in the range of preferably 0.01 to 25 mass%, more preferably 0.05 to 20 mass%, more preferably 0.1 to 18 mass%, more preferably 0.5 to 15 mass%, more preferably 1 to 12 mass%, more preferably 2 to 10 mass%, more preferably 3 to 8 mass%, more preferably 4 to 6 mass%, based on 100 mass% of the total amount of M, Y, X and O contained in the zeolitic material.
[0017] Preferably, using the zeolite material obtained from step (4), (4.i), or (4.ii), steps (3) and (4), and optionally (3.i), (3.ii), (3.iii), (4.i), and / or (4.ii) are repeated at least once; more preferably, steps (3) and (4), and optionally (3.i), (3.ii), (3.iii), (4.i), and / or (4.ii) are repeated 1 to 10 times, more preferably 1 to 8 times, more preferably 1 to 6 times, more preferably 1 to 4 times, more preferably 1 to 3 times, more preferably 1 to 2 times; more preferably, steps (3) and (4), and optionally (3.i), (3.ii), (3.iii), (4.i), and / or (4.ii) are repeated once.
[0018] The skeleton of the zeolite material provided in step (1) preferably has a Y:X molar ratio that falls within the range of 1 to 100, more preferably 1 to 50, more preferably 2 to 25, more preferably 3 to 12, and more preferably 4 to 6.
[0019] Preferably, Y is selected from the group consisting of Si, Sn, Ti, Zr, Ge, and mixtures of two or more thereof, and more preferably, Y is Si.
[0020] Preferably, X is selected from the group consisting of Al, B, In, Ga, and mixtures of two or more of these, and more preferably, X is Al.
[0021] The skeletal structure of the zeolite material provided in step (1) is preferably selected from the group consisting of AEI, BEA, CHA, DDR, ERI, FAU, FER, GME, HEU, LEV, MEI, MEL, MFI, MOR, MWW, and two or more mixed structures thereof; more preferably from the group consisting of AEI, BEA, CHA, FAU, FER, MFI, MOR, MWW, and two or more mixed structures thereof; more preferably from the group consisting of BEA, CHA, MOR, and two or more mixed structures thereof; more preferably, the zeolite material provided in step (1) has a BEA and / or CHA skeletal structure, preferably a BEA skeletal structure.
[0022] Preferably, the zeolite material provided in step (1) comprises one or more zeolites having a BEA-type skeletal structure selected from the group consisting of zeolite beta, beta polymorph B, [B-Si-O]-*BEA, chernicite, [Ga-Si-O]-*BEA, CIT-6, and mixtures of two or more thereof. More preferably, the zeolite material provided in step (1) comprises zeolite beta, and more preferably, the zeolite material provided in step (1) is zeolite beta.
[0023] The pH of the aqueous solution provided in step (2) is preferably in the range of -1 to 0.05, more preferably -0.8 to 0, more preferably -0.7 to -0.03, more preferably -0.6 to -0.05, more preferably -0.5 to -0.08, more preferably -0.4 to -0.1, more preferably -0.3 to -0.13, and more preferably -0.2 to -0.15, wherein the pH is preferably determined using a glass pH electrode, more preferably the pH is determined using a glass pH electrode in accordance with ISO 23497:2019, and more preferably the pH is determined in accordance with DIN 19268.
[0024] The aqueous solution provided in step (2) preferably has a pK of 2.5 or less, more preferably 2.3 or less, more preferably 2 or less, more preferably 1.8 or less, more preferably 1.5 or less, more preferably 1.3 or less, more preferably 1 or less, more preferably 0.8 or less, more preferably 0.5 or less, more preferably 0.3 or less, more preferably 0.1 or less, and more preferably 0 or less. a Contains one or more acids that have a value.
[0025] One or more acids are preferably from the group consisting of mineral acids, organic acids, and two or more mixtures thereof; more preferably from the group consisting of mineral acids and two or more mixtures thereof; more preferably from the group consisting of HCl, HBr, HI, HClO, HClO2, HClO3, HClO4, H2SO4, HSO3F, HNO3, H3PO4, HSBF6, HBF4, HPF6, and two or more mixtures thereof; more preferably HCl, HBr, HClO4, H2SO4, HSO3F, HNO3, H3PO4, and two or more of these. From the group consisting of the above mixtures, more preferably from the group consisting of HCl, HBr, H2SO4, HNO3, H3PO4, and mixtures of two or more thereof, more preferably from the group consisting of H2SO4, HNO3, H3PO4, and mixtures of two or more thereof, more preferably the aqueous solution provided in step (2) contains HNO3, more preferably the acid contained in the aqueous solution provided in step (2) is HNO3, and more preferably the aqueous solution provided in step (2) consists of distilled water and HNO3.
[0026] Preferably, the total concentration of one or more acids contained in the aqueous solution provided in step (2) is 0.8 mol / L or more, and more preferably, the total concentration of one or more acids contained in the aqueous solution provided in step (2) is in the range of 0.8 to 10 mol / L, more preferably 1.0 to 10 mol / L, more preferably 1.0 to 7.9 mol / L, more preferably 1.0 to 6.3 mol / L, more preferably 1.1 to 2.5 mol / L, more preferably 1.1 to 1.6 mol / L, and more preferably 1.1 to 1.4 mol / L.
[0027] The molar ratio H2O:Y of the amount of H2O in the aqueous solution provided in step (2) and used for processing in step (3) to the amount of Y in the skeletal structure of the zeolite material processed in step (3) is preferably in the range of 1 to 200, more preferably 3 to 150, more preferably 5 to 50, more preferably 7 to 25, more preferably 8 to 15, more preferably 8.5 to 12, more preferably 9 to 11, and more preferably 9.5 to 10.5.
[0028] The processing in step (3) is preferably carried out at a temperature within the range of 20 to 100°C, more preferably 30 to 90°C, more preferably 40 to 80°C, more preferably 50 to 70°C, more preferably 55 to 65°C, more preferably 58 to 62°C, and more preferably 59 to 61°C.
[0029] The process in step (3) is carried out for a duration that is preferably within the range of 40 to 200 minutes, more preferably 60 to 180 minutes, more preferably 70 to 170 minutes, more preferably 80 to 160 minutes, more preferably 90 to 150 minutes, more preferably 100 to 140 minutes, more preferably 110 to 130 minutes, and more preferably 115 to 125 minutes.
[0030] Preferably, the washing in any step (3.i) is carried out with distilled water.
[0031] Drying in any step (3.ii) is preferably carried out at a temperature within the range of 40 to 200°C, more preferably 60 to 180°C, more preferably 70 to 170°C, more preferably 80 to 160°C, more preferably 90 to 150°C, more preferably 100 to 140°C, more preferably 110 to 130°C, more preferably 115 to 125°C, and more preferably 118 to 122°C.
[0032] Drying in any step (3.ii) is preferably carried out for a duration within the range of 0.25 to 48 hours, more preferably 0.5 to 36 hours, more preferably 1 to 30 hours, more preferably 2 to 24 hours, more preferably 4 to 20 hours, more preferably 6 to 18 hours, more preferably 8 to 16 hours, more preferably 10 to 14 hours, and more preferably 11 to 13 hours.
[0033] The firing in any step (3.iii) is preferably carried out at a temperature within the range of 300-900°C, more preferably 350-850°C, more preferably 400-800°C, more preferably 450-750°C, more preferably 500-700°C, more preferably 550-650°C, more preferably 590-610°C, and more preferably 598-602°C.
[0034] The firing in any step (3.iii) is preferably carried out for a duration within the range of 1 to 10 hours, more preferably 2 to 8 hours, more preferably 3 to 7 hours, more preferably 4 to 6 hours, and more preferably 4.5 to 5.5 hours.
[0035] The pH of the aqueous solution or solvent system used in the treatment in step (4) is preferably in the range of 4 to 10, more preferably 5 to 9, more preferably 6 to 8, more preferably 6.5 to 7.5, and more preferably 6.8 to 7.2, where the pH of the aqueous solution or solvent system refers to the pH before contact with the zeolite material for treatment.
[0036] Preferably, the solvent system used in step (4) contains water, and more preferably, the solvent system used in step (4) consists of distilled water.
[0037] The processing in step (4) is preferably carried out at a temperature within the range of 30 to 150°C, more preferably 40 to 140°C, more preferably 50 to 130°C, more preferably 60 to 120°C, more preferably 70 to 110°C, more preferably 80 to 100°C, more preferably 85 to 95°C, and more preferably 88 to 92°C.
[0038] The processing in step (4) is preferably carried out for a duration within the range of 1 to 17 hours, more preferably 2 to 16 hours, more preferably 3 to 15 hours, more preferably 5 to 13 hours, more preferably 6 to 12 hours, more preferably 7 to 11 hours, more preferably 8 to 10 hours, and more preferably 8.5 to 9.5 hours.
[0039] Preferably, the solvent system includes water, where the molar ratio H2O:Y of the molar amount of H2O in the aqueous solution or solvent system used for processing in step (3) to the molar amount of Y in the skeletal structure of the zeolite material processed in step (3) is in the range of 1 to 250, more preferably 2.5 to 200, more preferably 5 to 150, more preferably 10 to 100, more preferably 15 to 50, more preferably 20 to 30, more preferably 21 to 26, and more preferably 22 to 24.
[0040] Drying in any step (4.i) is preferably carried out at a temperature within the range of 40-200°C, more preferably 50-190°C, more preferably 60-180°C, more preferably 70-170°C, more preferably 80-160°C, more preferably 90-150°C, more preferably 100-140°C, more preferably 110-130°C, more preferably 115-125°C, and more preferably 118-122°C.
[0041] Drying in any step (4.i) is preferably carried out for a duration within the range of 0.25 to 48 hours, more preferably 0.5 to 36 hours, more preferably 1 to 30 hours, more preferably 2 to 24 hours, more preferably 4 to 20 hours, more preferably 6 to 18 hours, more preferably 8 to 16 hours, more preferably 10 to 14 hours, and more preferably 11 to 13 hours.
[0042] The firing in any step (4.ii) is preferably carried out at a temperature within the range of 200 to 1000°C, more preferably 300 to 900°C, more preferably 350 to 850°C, more preferably 400 to 800°C, more preferably 450 to 750°C, more preferably 500 to 700°C, more preferably 550 to 650°C, more preferably 575 to 625°C, and more preferably 595 to 605°C.
[0043] The firing in any step (4.ii) is preferably carried out for a duration within the range of 1 to 10 hours, more preferably 2 to 8 hours, more preferably 3 to 7 hours, more preferably 4 to 6 hours, and more preferably 4.5 to 5.5 hours.
[0044] Preferably, the zeolite material provided in step (1) can be obtained by a synthesis method that does not use an organic template.
[0045] If the zeolite material provided in step (1) can be obtained by a synthesis method that does not use an organic template, then preferably the synthesis method that does not use an organic template is (A) A step of preparing a mixture containing one or more YO2 sources, one or more X2O3 sources, and a seed crystal containing one or more zeolite materials having a BEA-type skeletal structure, and (B) A step to crystallize the mixture obtained in step (A) in order to form a zeolite material having a BEA-type skeletal structure. Includes, Here, Y is a tetravalent element and X is a trivalent element. The mixture provided in step (A) and crystallized in step (B) does not contain an organic template as a structural indicator.
[0046] Preferably, the zeolite material obtained in step (B) contains one or more alkali metals M, where M is more preferably selected from the group consisting of Li, Na, K, Cs, and two or more combinations thereof, more preferably from the group consisting of Li, Na, K, and two or more combinations thereof, and more preferably the alkali metal M is Na and / or K, and even more preferably Na.
[0047] Preferably, Y is selected from the group consisting of Si, Sn, Ti, Zr, Ge, and mixtures of two or more thereof, and more preferably, Y is Si.
[0048] The one or more YO2 sources provided in step (A) preferably comprise one or more silicates, more preferably one or more alkali metal silicates, where the alkali metal is preferably selected from the group consisting of Li, Na, K, Rb, and Cs, more preferably the alkali metal is Na and / or K, and even more preferably the alkali metal is Na. Furthermore, the one or more YO2 sources preferably comprise one or more silicates in addition to one or more silicates, more preferably one or more silica hydrosols and / or one or more colloidal silica, and even more preferably one or more silicates in addition to one or more colloidal silica. In particular, the mixture provided in step (A) preferably comprises water glass, more preferably sodium silicate and / or potassium silicate, and more preferably sodium silicate.
[0049] Preferably, X is selected from the group consisting of Al, B, In, Ga, and mixtures of two or more of these, and more preferably, X is Al.
[0050] One or more X2O3 sources preferably comprise one or more aluminates, more preferably an alkali metal aluminate, where the alkali metal is preferably selected from the group consisting of Li, Na, K, Rb, and Cs, more preferably the alkali metal is Na and / or K, and even more preferably the alkali metal is Na.
[0051] The molar ratio YO2:X2O3 of the mixture obtained in step (A) is preferably in the range of 1 to 200, more preferably 5 to 100, more preferably 10 to 50, more preferably 15 to 40, more preferably 20 to 30, more preferably 23 to 25, and even more preferably 23.5 to 24.
[0052] The amount of seed crystals contained in the mixture from step (A) is preferably in the range of 0.1 to 30% by mass, more preferably 0.5 to 20% by mass, more preferably 1 to 10% by mass, more preferably 1.5 to 5% by mass, more preferably 2 to 4% by mass, and even more preferably 2.5 to 3.5% by mass, based on 100% by mass of YO2 from one or more YO2 sources.
[0053] Preferably, the mixture from step (A) further comprises one or more solvents, where the one or more solvents more preferably comprises water, and more preferably deionized water. Furthermore, the molar ratio H2O:YO2 of the mixture from step (A) is preferably in the range of 5 to 100, more preferably 10 to 50, more preferably 13 to 30, more preferably 15 to 20, and even more preferably 17 to 18.
[0054] The molar ratio M:YO2 in the mixture obtained in step (A) is preferably in the range of 0.05 to 5, more preferably 0.1 to 2, more preferably 0.3 to 1, more preferably 0.4 to 0.8, more preferably 0.45 to 0.7, more preferably 0.5 to 0.65, and even more preferably 0.55 to 0.6. Furthermore, the molar ratio YO2:X2O3:M in the mixture obtained in step (A) is preferably in the range of (1 to 200):1:(0.5 to 100), more preferably (5 to 100):1:(5 to 75), more preferably (10 to 50):1:(8 to 50), more preferably (15 to 40):1:(10 to 30), more preferably (20 to 30):1:(11 to 20), more preferably (23 to 25):1:(12 to 15), and even more preferably (23.5 to 24):1:(13 to 14).
[0055] Preferably, the crystallization in step (B) includes heating the mixture at a temperature in the range of more preferably 80 to 200°C, more preferably 90 to 180°C, more preferably 100 to 160°C, more preferably 110 to 140°C, and even more preferably 115 to 130°C.
[0056] Furthermore, preferably, the crystallization in step (B) is carried out under solvothermal conditions.
[0057] Furthermore, the crystallization in step (B) includes heating the mixture for a duration of preferably 5 to 200 hours, more preferably 20 to 160 hours, more preferably 60 to 140 hours, and even more preferably 100 to 130 hours.
[0058] Preferably, this method further includes one or more of the following steps: (C) A step of separating the zeolite material having a BEA-type skeletal structure obtained in step (B) preferably by filtration; and (D) Optionally, a step of washing the zeolite material having a BEA-type skeletal structure obtained in step (B) or (C); and / or (E) Optionally, a step of drying the zeolite material having a BEA-type skeletal structure obtained in step (B), (C), or (D).
[0059] Preferably, the zeolite material having a BEA-type skeletal structure formed in step (B) contains zeolite beta.
[0060] Preferably, the seed crystal comprises a zeolite material having a BEA-type skeletal structure that can or can be obtained according to the method of any one of the particular preferred embodiments of the present invention, and preferably the seed crystal comprises zeolite beta.
[0061] Preferably, this method further includes one or more of the following steps: (F) A step of subjecting the zeolite material having a BEA-type framework structure obtained in step (B), (C), (D), or (E) to an ion exchange procedure; and (G) A step of washing the ion-exchange zeolite material obtained in step (F); and / or (H) A step of drying and / or calcining the zeolite material having a BEA-type skeletal structure obtained in step (B), (C), (D), (E), (F), or (G).
[0062] If the method further includes step (F) of subjecting the zeolite material having a BEA-type skeleton structure obtained in step (B), (C), (D), or (E) to an ion exchange procedure, preferably in step (F) at least one ionic non-skeletal element in the zeolite material is H + and / or NH 4+ For more than NH 4+ Ion exchange occurs with respect to it.
[0063] In step (F), at least one ionic non-skeleton element in the zeolite material is H + and / or NH 4+ When ion-exchanged with respect to, preferably, at least one ionic non-skeleton element is H + The material comprises one or more cations selected from the group consisting of alkali metal cations, more preferably the alkali metal cation is selected from the group consisting of Li, Na, K, Cs and two or more combinations thereof, more preferably Li, Na, K and two or more combinations thereof, more preferably the alkali metal cation is Na and / or K, even more preferably Na, and more preferably at least one ionic nonskeletal element is Na, and more preferably at least one ionic nonskeletal element is Na.
[0064] Steps (F) and (G) are preferably repeated once or more, more preferably three or more times, more preferably two or more times, and more preferably, steps (F) and (G) are repeated once.
[0065] The drying in step (H) is preferably carried out at a temperature within the range of 40 to 200°C, more preferably 60 to 180°C, more preferably 70 to 170°C, more preferably 80 to 160°C, more preferably 90 to 150°C, more preferably 100 to 140°C, and more preferably 110 to 130°C.
[0066] The drying in step (H) is carried out for a duration preferably within the range of 0.25 to 48 hours, more preferably 0.5 to 42 hours, more preferably 1 to 36 hours, more preferably 2 to 32 hours, more preferably 4 to 28 hours, more preferably 6 to 24 hours, more preferably 10 to 20 hours, and more preferably 14 to 18 hours.
[0067] The firing in step (H) is preferably carried out at a temperature within the range of 200 to 900°C, more preferably 300 to 800°C, more preferably 350 to 750°C, more preferably 400 to 700°C, more preferably 450 to 650°C, more preferably 500 to 600°C, and more preferably 525 to 575°C.
[0068] The firing in step (H) is preferably carried out for a duration within the range of 1 to 10 hours, more preferably 2 to 8 hours, more preferably 3 to 7 hours, more preferably 4 to 6 hours, and more preferably 4.5 to 5.5 hours.
[0069] The present invention also relates to zeolite materials that can and / or be obtained according to a method described in any one of the particular preferred embodiments of the present invention.
[0070] The present invention is further illustrated by the following set of embodiments and combinations of embodiments arising from the dependencies and backreferences shown. In particular, it should be noted that in each example where the scope of an embodiment is referred to, for example, in the context of terms such as "the method according to any one of Embodiments 1 to 4", all embodiments within this scope are expressly disclosed to those skilled in the art, i.e., the wording of this term is understood to those skilled in the art to be synonymous with "the method according to any one of Embodiments 1, 2, 3, and 4". Furthermore, it should be explicitly noted that the following set of embodiments does not constitute a set of claims that determine the scope of protection, but rather represents a suitably configured portion of the description directed to the general and preferred aspects of the present invention.
[0071] 1. (1) A step of providing a zeolite material having a skeletal structure containing Y, X, and O, wherein Y is a tetravalent element and X is a trivalent element, (2) A step of providing an aqueous solution having a pH of less than 0.1, (3) A step of treating the zeolite material provided in step (1) with the aqueous solution provided in step (2), (3.i) Optionally, a step of washing the zeolite material obtained in step (3), (3.ii) optionally, drying the zeolitic material obtained in step (3) or (3.i), (3.iii) optionally, calcining the zeolitic material obtained in step (3), (3.i) or (3.ii), (4) treating the zeolitic material obtained in step (3), (3.i), (3.ii) or (3.iii) with an aqueous solution or solvent system, wherein the aqueous solution or solvent system has a pH in the range of 4 to 10, and the pH of the aqueous solution or solvent system refers to the pH before being brought into contact with the zeolitic material for the treatment, (4.i) optionally, drying the zeolitic material obtained in step (4), (4.ii) optionally, calcining the zeolitic material obtained in step (4) or (4.i), A process for dealuminating a zeolitic material, comprising the steps of.
[0072] 2. The process according to embodiment 1, wherein the zeolitic material provided in step (1) contains less than 1 wt.%, preferably less than 0.5 wt.%, more preferably less than 0.1 wt.%, more preferably less than 0.05 wt.%, more preferably less than 0.01 wt.%, more preferably less than 0.005 wt.%, more preferably less than 0.001 wt.% of H, based on 100 wt.% of the total amount of Y, X and O contained in the zeolitic material + ionic non-framework elements other than.
[0073] 3. The process according to embodiment 2, wherein the ionic non-framework elements represent Na, preferably Na and K, more preferably Li, Na and K, more preferably Li, Na, K and Cs, more preferably alkali metal cations, more preferably alkali metal and alkaline earth metal cations, more preferably metal cations.
[0074] 4. The method according to Embodiment 1, wherein the zeolite material provided in step (1) contains one or more metals M, and the one or more metals M is selected from the group consisting of alkali metals, alkaline earth metals, and mixtures of two or more thereof, preferably from the group consisting of alkali metals, more preferably from the group consisting of Li, Na, K, Rb, Cs, and mixtures of two or more thereof, more preferably from the group consisting of Li, Na, K, and mixtures of two or more thereof, and more preferably the one or more metals M contains Na and / or K, preferably Na, and more preferably the one or more metals M consists of Na and / or K, preferably Na.
[0075] 5. The method according to Embodiment 4, wherein the zeolite material provided in step (1) contains one or more alkali metals or alkaline earth metals in an amount ranging from 0.01 to 25% by mass, preferably 0.05 to 20% by mass, more preferably 0.1 to 18% by mass, more preferably 0.5 to 15% by mass, more preferably 1 to 12% by mass, more preferably 2 to 10% by mass, more preferably 3 to 8% by mass, and more preferably 4 to 6% by mass, based on 100% by mass of the total amount of M, Y, X, and O contained in the zeolite material.
[0076] 6. The method according to any one of Embodiments 1 to 5, wherein steps (3) and (4), and optionally (3) (i), (3) (ii), (3) (iii), (4) (i) and / or (4) (ii) (1) to 10 times, more preferably 1 to 8 times, more preferably 1 to 6 times, more preferably 1 to 4 times, more preferably 1 to 3 times, more preferably 1 to 2 times, and more preferably steps (3) and (4), and optionally (3) (ii), (3) (ii), (3) (iii), (4) (i) and / or (4) (ii) (1) to 10 times.
[0077] 7. The method according to any one of Embodiments 1 to 6, wherein the skeleton of the zeolite material provided in step (1) has a Y:X molar ratio in the range of 1 to 100, preferably 1 to 50, more preferably 2 to 25, more preferably 3 to 12, and more preferably 4 to 6.
[0078] 8. The method according to any one of Embodiments 1 to 7, wherein Y is selected from the group consisting of Si, Sn, Ti, Zr, Ge, and mixtures of two or more thereof, and preferably Y is Si.
[0079] 9. The method according to any one of Embodiments 1 to 8, wherein X is selected from the group consisting of Al, B, In, Ga, and mixtures of two or more thereof, and preferably X is Al.
[0080] 10. The method according to any one of Embodiments 1 to 9, wherein the skeletal structure of the zeolite material provided in step (1) is selected from the group consisting of AEI, BEA, CHA, DDR, ERI, FAU, FER, GME, HEU, LEV, MEI, MEL, MFI, MOR, MWW, and two or more mixed structures thereof, preferably from the group consisting of AEI, BEA, CHA, FAU, FER, MFI, MOR, MWW, and two or more mixed structures thereof, more preferably from the group consisting of BEA, CHA, MOR, and two or more mixed structures thereof, and more preferably the method according to any one of Embodiments 1 to 9, wherein the zeolite material provided in step (1) has a BEA and / or CHA skeletal structure, preferably a BEA skeletal structure.
[0081] 11. The method according to any one of Embodiments 1 to 10, wherein the zeolite material provided in step (1) comprises one or more zeolites having a BEA-type skeletal structure selected from the group consisting of zeolite beta, beta polymorph B, [B-Si-O]-*BEA, chernicite, [Ga-Si-O]-*BEA, CIT-6, and mixtures of two or more thereof, preferably the zeolite material provided in step (1) comprises zeolite beta, and more preferably the zeolite material provided in step (1) is zeolite beta.
[0082] 12. The method according to any one of Embodiments 1 to 11, wherein the pH of the aqueous solution provided in step (2) is in the range of -1 to 0.05, preferably -0.8 to 0, more preferably -0.7 to -0.03, more preferably -0.6 to -0.05, more preferably -0.5 to -0.08, more preferably -0.4 to -0.1, more preferably -0.3 to -0.13, and more preferably -0.2 to -0.15, and preferably the pH is determined using a glass pH electrode, more preferably the pH is determined using a glass pH electrode in accordance with ISO 23497:2019, and more preferably the pH is determined in accordance with DIN 19268.
[0083] 13. The aqueous solution provided in step (2) has a pK of 2.5 or less, preferably 2.3 or less, more preferably 2 or less, more preferably 1.8 or less, more preferably 1.5 or less, more preferably 1.3 or less, more preferably 1 or less, more preferably 0.8 or less, more preferably 0.5 or less, more preferably 0.3 or less, more preferably 0.1 or less, and more preferably 0 or less. a The method according to any one of Embodiments 1 to 12, comprising one or more acids having a value.
[0084] 14. The one or more acids are preferably from the group consisting of mineral acids, organic acids, and mixtures of two or more thereof, more preferably from the group consisting of mineral acids and mixtures of two or more thereof, more preferably from the group consisting of HCl, HBr, HI, HClO, HClO2, HClO3, HClO4, H2SO4, HSO3F, HNO3, H3PO4, HSBF6, HBF4, HPF6, and mixtures of two or more thereof, more preferably from the group consisting of HCl, HBr, HClO4, H2SO4, HSO3F, HNO3, H3PO4, and mixtures of two or more thereof. The method according to any one of Embodiments 1 to 13, wherein the aqueous solution is preferably selected from the group consisting of HCl, HBr, H2SO4, HNO3, H3PO4, and mixtures of two or more thereof, more preferably selected from the group consisting of H2SO4, HNO3, H3PO4, and mixtures of two or more thereof, more preferably the aqueous solution provided in step (2) contains HNO3, more preferably the acid contained in the aqueous solution provided in step (2) is HNO3, and more preferably the aqueous solution provided in step (2) consists of distilled water and HNO3.
[0085] 15. The method according to Embodiment 13 or 14, wherein the total concentration of the one or more acids contained in the aqueous solution provided in step (2) is 0.8 mol / L or more, preferably the total concentration of the one or more acids contained in the aqueous solution provided in step (2) is in the range of 0.8 to 10 mol / L, more preferably 1.0 to 10 mol / L, more preferably 1.0 to 7.9 mol / L, more preferably 1.0 to 6.3 mol / L, more preferably 1.1 to 2.5 mol / L, more preferably 1.1 to 1.6 mol / L, and more preferably 1.1 to 1.4 mol / L.
[0086] 16. The method according to any one of Embodiments 1 to 15, wherein the molar ratio H2O:Y of the amount of H2O in the aqueous solution provided in step (2) and used for processing in step (3) to the amount of Y in the skeletal structure of the zeolite material processed in step (3) is in the range of 1 to 200, preferably 3 to 150, more preferably 5 to 50, more preferably 7 to 25, more preferably 8 to 15, more preferably 8.5 to 12, more preferably 9 to 11, and more preferably 9.5 to 10.5.
[0087] 17. The method according to any one of Embodiments 1 to 16, wherein the processing in step (3) is carried out at a temperature within the range of 20 to 100°C, preferably 30 to 90°C, more preferably 40 to 80°C, more preferably 50 to 70°C, more preferably 55 to 65°C, more preferably 58 to 62°C, and more preferably 59 to 61°C.
[0088] 18. The method according to any one of Embodiments 1 to 17, wherein the processing in step (3) is carried out for a duration that falls within the range of 40 to 200 minutes, preferably 60 to 180 minutes, more preferably 70 to 170 minutes, more preferably 80 to 160 minutes, more preferably 90 to 150 minutes, more preferably 100 to 140 minutes, more preferably 110 to 130 minutes, and more preferably 115 to 125 minutes.
[0089] 19. The method according to any one of Embodiments 1 to 18, wherein the washing in any step (3.i) is performed with distilled water.
[0090] 20. The method according to any one of Embodiments 1 to 19, wherein the drying in any step (3.ii) is carried out at a temperature within the range of 40 to 200°C, preferably 60 to 180°C, more preferably 70 to 170°C, more preferably 80 to 160°C, more preferably 90 to 150°C, more preferably 100 to 140°C, more preferably 110 to 130°C, more preferably 115 to 125°C, and more preferably 118 to 122°C.
[0091] 21. The method according to any one of Embodiments 1 to 20, wherein the drying in any step (3.ii) is carried out for a duration that falls within the range of 0.25 to 48 hours, preferably 0.5 to 36 hours, more preferably 1 to 30 hours, more preferably 2 to 24 hours, more preferably 4 to 20 hours, more preferably 6 to 18 hours, more preferably 8 to 16 hours, more preferably 10 to 14 hours, and more preferably 11 to 13 hours.
[0092] 22. The method according to any one of Embodiments 1 to 21, wherein the firing in any step (3.iii) is carried out at a temperature within the range of 300 to 900°C, preferably 350 to 850°C, more preferably 400 to 800°C, more preferably 450 to 750°C, more preferably 500 to 700°C, more preferably 550 to 650°C, more preferably 590 to 610°C, and more preferably 598 to 602°C.
[0093] 23. The method according to any one of Embodiments 1 to 22, wherein the firing in any step (3.iii) is carried out for a duration that falls within the range of 1 to 10 hours, preferably 2 to 8 hours, more preferably 3 to 7 hours, more preferably 4 to 6 hours, and more preferably 4.5 to 5.5 hours.
[0094] 24. The method according to any one of Embodiments 1 to 23, wherein the pH of the aqueous solution or solvent system used in the treatment in step (4) is in the range of 4 to 10, preferably 5 to 9, more preferably 6 to 8, more preferably 6.5 to 7.5, and more preferably 6.8 to 7.2, and the pH of the aqueous solution or solvent system refers to the pH before contact with the zeolite material for treatment.
[0095] 25. The method according to any one of Embodiments 1 to 24, wherein the solvent system used in step (4) contains water, and preferably the solvent system used in step (4) consists of distilled water.
[0096] 26. The method according to any one of Embodiments 1 to 25, wherein the processing in step (4) is carried out at a temperature within the range of 30 to 150°C, preferably 40 to 140°C, more preferably 50 to 130°C, more preferably 60 to 120°C, more preferably 70 to 110°C, more preferably 80 to 100°C, more preferably 85 to 95°C, and more preferably 88 to 92°C.
[0097] 27. The method according to any one of embodiments 1 to 26, wherein the processing in step (4) is carried out for a duration that falls within the range of 1 to 17 hours, preferably 2 to 16 hours, more preferably 3 to 15 hours, more preferably 5 to 13 hours, more preferably 6 to 12 hours, more preferably 7 to 11 hours, more preferably 8 to 10 hours, and more preferably 8.5 to 9.5 hours.
[0098] 28. The method according to any one of Embodiments 1 to 27, wherein the solvent system contains water, and the molar ratio H2O:Y of the molar amount of H2O in the aqueous solution or solvent system used for processing in step (3) to the molar amount of Y in the skeletal structure of the zeolite material processed in step (3) is in the range of 1 to 250, preferably 2.5 to 200, more preferably 5 to 150, more preferably 10 to 100, more preferably 15 to 50, more preferably 20 to 30, more preferably 21 to 26, and more preferably 22 to 24.
[0099] 29. The method according to any one of Embodiments 1 to 28, wherein the drying in any step (4.i) is carried out at a temperature within the range of 40 to 200°C, preferably 50 to 190°C, more preferably 60 to 180°C, more preferably 70 to 170°C, more preferably 80 to 160°C, more preferably 90 to 150°C, more preferably 100 to 140°C, more preferably 110 to 130°C, more preferably 115 to 125°C, and more preferably 118 to 122°C.
[0100] 30. The method according to any one of Embodiments 1 to 29, wherein drying in any step (4.i) is carried out for a duration that falls within the range of 0.25 to 48 hours, preferably 0.5 to 36 hours, more preferably 1 to 30 hours, more preferably 2 to 24 hours, more preferably 4 to 20 hours, more preferably 6 to 18 hours, more preferably 8 to 16 hours, more preferably 10 to 14 hours, and more preferably 11 to 13 hours.
[0101] 31. The method according to any one of Embodiments 1 to 30, wherein the firing in any step (4.ii) is carried out at a temperature within the range of 200 to 1000°C, preferably 300 to 900°C, more preferably 350 to 850°C, more preferably 400 to 800°C, more preferably 450 to 750°C, more preferably 500 to 700°C, more preferably 550 to 650°C, more preferably 575 to 625°C, and more preferably 595 to 605°C.
[0102] 32. The method according to any one of Embodiments 1 to 31, wherein the firing in any step (4.ii) is carried out for a duration that falls within the range of 1 to 10 hours, preferably 2 to 8 hours, more preferably 3 to 7 hours, more preferably 4 to 6 hours, and more preferably 4.5 to 5.5 hours.
[0103] 33. The method according to any one of Embodiments 1 to 32, wherein the zeolite material provided in step (1) can be obtained or is obtained by a synthesis method that does not use an organic template.
[0104] 34. The synthesis method that does not use the organic template is (A) A step of preparing a mixture containing one or more YO2 sources, one or more X2O3 sources, and a seed crystal containing one or more zeolite materials having a BEA-type skeletal structure, and (B) A step to crystallize the mixture obtained in step (A) in order to form a zeolite material having a BEA-type skeletal structure. Includes, Y is a tetravalent element, and X is a trivalent element. The method according to Embodiment 33, wherein the mixture provided in step (A) and crystallized in step (B) does not contain an organic template as a structural indicator.
[0105] 35. The method according to Embodiment 34, wherein the zeolite material obtained in step (B) contains one or more alkali metals M, and M is preferably selected from the group consisting of Li, Na, K, Cs, and two or more combinations thereof, more preferably from the group consisting of Li, Na, K, and two or more combinations thereof, and more preferably the alkali metal M is Na and / or K, and even more preferably Na.
[0106] 36. The method according to Embodiment 34 or 35, wherein Y is selected from the group consisting of Si, Sn, Ti, Zr, Ge, and mixtures of two or more thereof, and preferably Y is Si.
[0107] 37. The method according to any one of embodiments 34 to 36, wherein the one or more YO2 sources provided in step (A) comprises one or more silicates, preferably one or more alkali metal silicates, wherein the alkali metal is preferably selected from the group consisting of Li, Na, K, Rb, and Cs, more preferably the alkali metal is Na and / or K, and even more preferably the alkali metal is Na.
[0108] 38. The method according to Embodiment 37, wherein the YO2 source comprises one or more silicates in addition to one or more silicates, preferably one or more silica hydrosols and / or one or more colloidal silica, and more preferably one or more silicates in addition to one or more colloidal silica.
[0109] 39. The method according to Embodiment 37 or 38, wherein the mixture provided in step (A) comprises water glass, preferably sodium silicate and / or potassium silicate, more preferably sodium silicate.
[0110] 40. The method according to any one of embodiments 34 to 39, wherein X is selected from the group consisting of Al, B, In, Ga, and mixtures of two or more thereof, and preferably X is Al.
[0111] 41. The method according to any one of embodiments 34 to 40, wherein the one or more X2O3 sources comprises one or more aluminates, preferably alkali metal aluminates, wherein the alkali metal is preferably selected from the group consisting of Li, Na, K, Rb, and Cs, more preferably the alkali metal is Na and / or K, and even more preferably the alkali metal is Na.
[0112] 42. The method according to any one of embodiments 34 to 41, wherein the molar ratio YO2:X2O3 of the mixture obtained in step (A) is in the range of 1 to 200, preferably 5 to 100, more preferably 10 to 50, more preferably 15 to 40, more preferably 20 to 30, more preferably 23 to 25, and even more preferably 23.5 to 24.
[0113] 43. The method according to any one of embodiments 34 to 42, wherein the amount of seed crystals contained in the mixture by step (A) is in the range of 0.1 to 30% by mass, preferably 0.5 to 20% by mass, more preferably 1 to 10% by mass, more preferably 1.5 to 5% by mass, more preferably 2 to 4% by mass, and even more preferably 2.5 to 3.5% by mass, based on 100% by mass of YO2 in the one or more YO2 sources.
[0114] 44. The method according to any one of embodiments 34 to 43, wherein the mixture obtained in step (A) further comprises one or more solvents, the one or more solvents preferably comprising water, more preferably deionized water.
[0115] 45. The method according to Embodiment 44, wherein the molar ratio H2O:YO2 of the mixture obtained in step (A) is in the range of 5 to 100, preferably 10 to 50, more preferably 13 to 30, more preferably 15 to 20, and even more preferably 17 to 18.
[0116] 46. The method according to any one of Embodiments 34 to 45, wherein the molar ratio M:YO2 in the mixture obtained by step (A) is in the range of 0.05 to 5, preferably 0.1 to 2, more preferably 0.3 to 1, more preferably 0.4 to 0.8, more preferably 0.45 to 0.7, more preferably 0.5 to 0.65, and even more preferably 0.55 to 0.6.
[0117] 47. The method according to Embodiment 46, wherein the molar ratio YO2:X2O3:M in the mixture obtained by step (A) is in the range of (1~200):1:(0.5~100), preferably (5~100):1:(5~75), more preferably (10~50):1:(8~50), more preferably (15~40):1:(10~30), more preferably (20~30):1:(11~20), more preferably (23~25):1:(12~15), and even more preferably (23.5~24):1:(13~14).
[0118] 48. The method according to any one of embodiments 35 to 47, wherein the crystallization in step (B) is preferably performed by heating the mixture at a temperature in the range of 80 to 200°C, more preferably 90 to 180°C, more preferably 100 to 160°C, more preferably 110 to 140°C, and even more preferably 115 to 130°C.
[0119] 49. The method according to Embodiment 48, wherein the crystallization in step (B) is carried out under solvothermal conditions.
[0120] 50. The method according to Embodiment 48 or 49, wherein the crystallization in step (B) comprises heating the mixture for a duration ranging from 5 to 200 hours, more preferably 20 to 160 hours, more preferably 60 to 140 hours, and even more preferably 100 to 130 hours.
[0121] 51. The above method comprises the following steps: (C) A step of separating the zeolite material having a BEA-type skeletal structure obtained in step (B) preferably by filtration; and (D) Optionally, a step of washing the zeolite material having a BEA-type skeletal structure obtained in step (B) or (C); and / or (E) Optionally, a step of drying the zeolite material having a BEA-type skeletal structure obtained in step (B), (C), or (D). The method according to any one of embodiments 34 to 50, further comprising one or more of the above.
[0122] 52. The method according to any one of embodiments 34 to 51, wherein the zeolite material having a BEA-type skeletal structure formed in step (B) includes zeolite beta.
[0123] 53. The method according to any one of Embodiments 34 to 52, wherein the seed crystal comprises a zeolite material having a BEA-type skeletal structure that can be obtained or obtained according to the method of any one of Embodiments 30 to 48, and preferably the seed crystal comprises zeolite beta.
[0124] 54. The above method comprises the following steps: (F) A step of subjecting the zeolite material having a BEA-type framework structure obtained in step (B), (C), (D), or (E) to an ion exchange procedure; and (G) A step of washing the ion-exchange zeolite material obtained in step (F); and / or (H) A process of drying and / or calcining the zeolite material having a BEA-type skeletal structure obtained in step (B), (C), (D), (E), (F), or (G). The method according to any one of embodiments 34 to 53, further comprising one or more of the above.
[0125] 55. In step (F), at least one ionic non-skeleton element in the zeolite material is H + and / or NH 4+ For more than NH 4+ The method according to embodiment 54, wherein ion exchange is performed with respect to the object.
[0126] 56. The above-mentioned at least one ionic non-skeleton element is H +The method according to Embodiment 55, comprising one or more cations selected from the group consisting of and alkali metal cations, preferably the alkali metal cation is selected from the group consisting of Li, Na, K, Cs and two or more combinations thereof, more preferably from the group consisting of Li, Na, K and two or more combinations thereof, more preferably the alkali metal cation is Na and / or K, even more preferably Na, more preferably the at least one ionic nonskeletal element comprises Na, and more preferably the at least one ionic nonskeletal element is Na.
[0127] 57. The method according to any one of embodiments 54 to 56, wherein steps (F) and (G) are repeated one or more times, preferably three or more times, more preferably two or more times, and more preferably steps (F) and (G) are repeated once.
[0128] 58. The method according to any one of embodiments 54 to 57, wherein the drying in step (H) is carried out at a temperature in the range of 40 to 200°C, preferably 60 to 180°C, more preferably 70 to 170°C, more preferably 80 to 160°C, more preferably 90 to 150°C, more preferably 100 to 140°C, and more preferably 110 to 130°C.
[0129] 59. The method according to any one of embodiments 54 to 58, wherein the drying in step (H) is carried out for a duration that falls within the range of 0.25 to 48 hours, preferably 0.5 to 42 hours, more preferably 1 to 36 hours, more preferably 2 to 32 hours, more preferably 4 to 28 hours, more preferably 6 to 24 hours, more preferably 10 to 20 hours, and more preferably 14 to 18 hours.
[0130] 60. The method according to any one of embodiments 54 to 59, wherein the firing in step (H) is carried out at a temperature within the range of 200 to 900°C, preferably 300 to 800°C, more preferably 350 to 750°C, more preferably 400 to 700°C, more preferably 450 to 650°C, more preferably 500 to 600°C, and more preferably 525 to 575°C.
[0131] 61. The method according to any one of embodiments 54 to 60, wherein the firing in step (H) is carried out for a duration that falls within the range of 1 to 10 hours, preferably 2 to 8 hours, more preferably 3 to 7 hours, more preferably 4 to 6 hours, and more preferably 4.5 to 5.5 hours.
[0132] 62. A zeolite material obtained and / or that can be obtained according to the method described in any one of Embodiments 1 to 60. [Examples]
[0133] Example 1: Determination of Crystallinity Powder X-ray diffraction (PXRD) data were collected using a diffractometer (D8 Advance Series II, Bruker AXS GmbH) equipped with a LYNXEYE detector operating in a copper anode X-ray tube operating at 40 kV and 40 mA. The geometry was Bragg-Brentano, and air scattering was reduced using an air scattering shield. Crystallinity was determined using DIFFRAC.EVA software (DIFFRAC.EVA user manual, Bruker AXS GmbH, Karlsruhe).
[0134] Reference Example 2: General Procedure for Dealuminization of Zeolite Materials Generally, the dealuminization procedure used four different processing steps, each with a different number of repetitions and order of processing steps: 1. (Acid)aluminization: Suspend zeolite powder in an acid solution (solid:liquid ratio of 1:3; for example, 50g of zeolite powder suspended in 150g of aqueous HNO3) and heat to the desired temperature. After the specified treatment time, allow the suspension to cool, filter it, and test the filtrate until the pH of the filtrate becomes neutral (in the case of H3PO4 and H2SO4 acid treatment), or use nitrate test paper (Merck KGaA) to test for NO3 - The filter was washed on a porcelain filter until no more traces were detected. Unless otherwise specified, the processing temperature and time were 60°C for 2 hours.
[0135] 2. Drying: The filtered cake was dried overnight in a convection oven at 120°C.
[0136] 3. Water treatment: Zeolite powder was suspended in water in a 1L four-necked round-bottom flask, heated under reflux at 90°C for 9 hours using an electric heating jacket, then filtered and dried (overnight at 120°C).
[0137] 4. Firing: Unless otherwise specified, the dried zeolite powder was fired in air in a static oven for firing at a heating rate of 2°C / min to 600°C for 5 hours.
[0138] Reference Example 3: Synthesis of Na-form zeolite materials without the use of organic templates 335.1 g of NaAlO2 was dissolved in 7314 g of H2O while stirring, followed by the addition of 74.5 g of zeolite beta species (commercially available from Zeolyst International, Valley Forge, PA 19482, USA, under the trade name CP814C, CAS registry number 1318-02-1). This mixture was placed in a 20 L autoclave, and 7340 g of sodium aqueous glass and 1436 g of Ludox AS40 were added. The resulting aluminosilicate gel was crystallized at 120°C for 117 hours. After the reaction mixture was cooled to room temperature, the solid was separated by filtration, washed repeatedly with distilled water, and dried at 120°C for 16 hours. The obtained material had a water absorption rate of 12% by mass.
[0139] Reference Example 4: Synthesis of H-morphological zeolite materials without the use of organic templates For the preparation of the H-form, 1000 g of zeolite material prepared according to Reference Example 3 was added to 10 g of a 10% by mass ammonium nitrate solution. The suspension was heated to 80°C and maintained at this temperature for 2 hours under continuous stirring. The solid was filtered while still hot (without further cooling) using a filter press. Next, the filtered cake was washed with distilled water (room temperature washing water) until the conductivity of the washing water was 200 microsiemens / cm or less. The filtered cake was dried at 120°C for 16 hours. This procedure was repeated once to obtain the ion-exchanged ammonium-form crystalline product BEA. The next calcination step at 500°C for 5 hours (heating rate of 1°C / min) yielded the H-form ion-exchanged crystalline product BEA.
[0140] Comparative Example 1: Dealuminization of zeolite beta with conventional acid concentration Zeolite beta obtained from the synthesis without the organic template described in Reference Example 4 was dealuminized using 4% HNO3 (pH=0.19 measured at 20°C according to DIN 19268) according to the method described in Reference Example 2. After dealuminization in step 1, the material was dried according to step 2, calcined according to step 4, treated with water according to step 3 (zeolite powder suspended in water in a solid:liquid ratio of 1:7), and finally dried again according to step 2. The entire series of steps was then repeated once to obtain dealuminized zeolite beta with a molar ratio of SiO2:Al2O3 of 19 and a degree of crystallinity of 73%.
[0141] Example 1: Dealuminization of zeolite beta with high-concentration acid Zeolite beta obtained from the synthesis without the organic template described in Reference Example 4 was dealuminized using 8% HNO3 (pH = -0.17 measured at 20°C according to DIN 19268) according to the method described in Reference Example 2. After dealuminization in step 1, the material was dried according to step 2, treated with water according to step 3 (zeolite powder suspended in water in a solid:liquid ratio of 1:10), and finally dried again according to step 2. This procedure yielded dealuminized zeolite beta with a molar ratio of SiO2:Al2O3 of 17.4 and a crystallinity of 76%.
[0142] Example 2: Dealuminization of zeolite beta with high-concentration acid Zeolite beta obtained from the synthesis without the organic template of Reference Example 4 was dealuminized using 8% HNO3 (pH = -0.17 measured at 20°C according to DIN 19268) according to the method described in Reference Example 2. After dealuminization in step 1, the material was dried according to step 2, treated with water according to step 3 (zeolite powder suspended in water in a solid:liquid ratio of 1:10), and finally dried again according to step 2. The entire series of steps was then repeated once to obtain dealuminized zeolite beta with a molar ratio of SiO2:Al2O3 of 61 and a crystallinity of 80%.
[0143] Example 3: Dealuminization of zeolite beta with high-concentration acid Zeolite beta obtained from the synthesis without using the organic template in Reference Example 4 was dealuminized using 8% HNO3 (pH = -0.17 measured at 20°C according to DIN 19268) according to the method described in Reference Example 2. After dealuminization in step 1, the material was dried according to step 2, treated with water according to step 3 (zeolite powder suspended in water in a solid:liquid ratio of 1:10), dried again according to step 2, and finally calcined according to step 4. The entire series of steps was then repeated once to obtain dealuminized zeolite beta with a molar ratio of SiO2:Al2O3 of 64 and a degree of crystallinity of 80%.
[0144] Therefore, as can be seen from the results obtained in Example 1 and Comparative Example 1, it was surprisingly found that by using a high concentration of acid, the same level of dealuminization as when using conventional concentrations of acid in a process involving two dealuminization steps could be achieved in just one dealuminization step. In particular, quite unexpectedly, it was found that, despite using a high concentration of acid in the method of the present invention, the loss of crystallinity was comparable, if not more significant, to that when using conventional concentrations of acid in the dealuminization step.
[0145] Furthermore, quite unexpectedly, it was found that a highly dealuminized olite material could be obtained by repeating the procedure of the present invention just once. Again, quite unexpectedly, even after repeating the dealuminization process with a high concentration of acid, the loss of crystallinity was found to be comparable, if not significantly so, to that obtained when the procedure was repeated with conventional concentrations of acid that could not achieve the same degree of dealuminization in the resulting material. Moreover, as shown by the comparison of the results of Comparative Example 1 and Example 1, and the results of Example 2 and Example 3, quite surprisingly, these unexpected results could even be achieved without using a calcination step in the procedure, thus resulting in an even higher level of time and cost efficiency compared to the procedure of Comparative Example 1.
[0146] References - EP 0 013 433 A1 - WO 02 / 057181 A2 - WO 2009 / 016153 A2 - WO 2012 / 137132 A1 - WO 2014 / 060260 A1
Claims
1. (1) A step of providing a zeolite material having a skeletal structure including Y, X, and O, wherein Y is Si and X is Al, (2) A step of providing an aqueous solution having a pH of less than 0.1, (3) A step of treating the zeolite material provided in step (1) with the aqueous solution provided in step (2), (3.i) Optionally, a step of washing the zeolite material obtained in step (3), (3.ii) Optionally, a step of drying the zeolite material obtained in step (3) or (3.i), (3.iii) Optionally, a step of firing the zeolite material obtained in step (3), (3.i), or (3.ii), (4) A step of treating the zeolite material obtained in step (3), (3.i), (3.ii) or (3.iii) with an aqueous solution or solvent system, wherein the aqueous solution or solvent system has a pH in the range of 4 to 10, the pH of the aqueous solution or solvent system refers to the pH before contact with the zeolite material for treatment, and the treatment is carried out at a temperature in the range of 30 to 150°C and for a time in the range of 1 to 17 hours. (4.i) Optionally, a step of drying the zeolite material obtained in step (4), (4.ii) Optionally, a step of firing the zeolite material obtained in step (4) or (4.i), A method for dealuminizing zeolite materials, including the method described above.
2. The method according to claim 1, wherein the zeolite material provided in step (1) contains less than 1% by mass of ionic non-skeletal elements other than H+ based on 100% by mass of the total amount of Y, X, and O contained in the zeolite material.
3. The method according to claim 2, wherein the ionic non-skeleton element represents Na.
4. The method according to claim 1, wherein the zeolite material provided in step (1) contains one or more metals M, and the one or more metals M are selected from the group consisting of alkali metals, alkaline earth metals, and mixtures of two or more thereof.
5. The method according to claim 4, wherein the zeolite material provided in step (1) contains one or more alkali metals or alkaline earth metals in an amount ranging from 0.01 to 25% by mass, based on 100% by mass of the total amount of M, Y, X, and O contained in the zeolite material.
6. The method according to any one of claims 1 to 5, wherein the skeletal structure of the zeolite material provided in step (1) is selected from the group consisting of AEI, BEA, CHA, DDR, ERI, FAU, FER, GME, HEU, LEV, MEI, MEL, MFI, MOR, MWW, and two or more mixed structures thereof.
7. The method according to any one of claims 1 to 6, wherein the zeolite material provided in step (1) comprises one or more zeolites having a BEA-type skeletal structure selected from the group consisting of zeolite beta, beta polymorph B, [B-Si-O]-*BEA, chernicite, [Ga-Si-O]-*BEA, CIT-6, and mixtures of two or more thereof.
8. The method according to any one of claims 1 to 7, wherein the pH of the aqueous solution provided in step (2) is in the range of -1 to 0.
05.
9. The method according to any one of claims 1 to 8, wherein the aqueous solution provided in step (2) contains one or more acids having a pKa value of 2.5 or less.
10. The method according to any one of claims 1 to 9, wherein the processing in step (3) is carried out for a duration that falls within the range of 40 to 200 minutes.
11. The method according to any one of claims 1 to 10, wherein the pH of the aqueous solution or solvent system used in the process in step (4) is in the range of 5 to 9, and the pH of the aqueous solution or solvent system refers to the pH before contact with the zeolite material for processing.
12. The method according to any one of claims 1 to 11, wherein the zeolite material provided in step (1) can be obtained or is obtained by a synthesis method that does not use an organic template.
Citation Information
Patent Citations
Heat oxidation resistant material based on silicon nitride and method of making this material
EP0013433A1
Method of dealuminizing large-pore diameter zeolite, catalyst and organophilic selective adsorbent containing dealuminized zeolite obtained by said method and silica- based zeolite beta
JP1992342415A
Novel proton type beta-zeolite
JP2004352578A
Method for producing dealuminated zeolitic material with bea framework structure
JP2018506500A
Hydrophobic zeolite, and method for producing the same
JP2021020211A